Early post-rift depositional systems of the Central Atlantic: Lower and Middle Jurassic of the Essaouira-Agadir Basin, Morocco. (June 2021) - Duval-Arnould, Aude; Schröder, Stefan; Charton, Rémi; Joussiaume, Rémi; Razin, Philippe; Redfern, Jonathan
Abstract: Passive margins are traditionally regarded as tectonically quiescent, however the increasing recognition of significant post-rift tectonic uplift along their flanks offers an important control on sediment delivery. The most extensive record of the early post-rift succession of the Central Atlantic Margin (CAM) is found in the Lower and Middle Jurassic outcrops of the Essaouira-Agadir Basin (EAB). This important succession is characterised by alternating deposition of marine carbonates and paralic siliciclastics that correlate with periods of tectonic activity along the margin, rejuvenating sediment input to the basin. Field observations, well data and petrographic analysis are integrated into a coherent sedimentological model, correlated across the basin within a sequence stratigraphic framework. Comparison is drawn with equivalent dated units in the Central High Atlas, which allows a constraint on the regional versus local tectonostratigraphic evolution. In the EAB, Upper Sinemurian to Lower Pliensbachian open marine ramp carbonates record an initial transgression. They are only preserved locally in the north of the basin, below a major fluvial erosion surface that is regionally traceable across the basin and incisive into the Pliensbachian, CAMP basalts or Triassic sediments. In the Central High Atlas (CHA), the correlative fluvial erosive event has been dated as Toarcian in age. This influx of siliciclastic sediments is interpreted to have been sourced from the Meseta and/or the Anti-Atlas, supporting recent apatite-fission track thermochronology that indicates erosional exhumation at this time. During the Upper Toarcian, a regional carbonate platform, dominated by peritidal deposits, developed across the EAB in response to renewed marine transgression. Facies include oolitic and bioclastic grainstones, crystalline dolomite, stromatolites and dissolution breccias or evaporites. Overlying Middle Jurassic shallow-marine and fluvial siliciclastics encroached from south of the basin (possibly related to a potential source area in the Anti-Atlas), while to the north shallow marine carbonates dominated. These observations evidence the role of tectonic movements of the hinterland during a passive margin phase as a mechanism to trigger forced regressions, compensating the effect of eustasy. Highlights: Detailed facies analysis of peritidal carbonates and continental deposits. Three transgression-regression cycles during the Lower and Middle Jurassic. Mixed carbonate-siliciclastic system influenced by tectonic movements. Siliciclastic deposits along the passive margin correlate with exhumation periods. Parallel evolution of the Western High Atlas and Central High Atlas.